Effect of arbuscular mycorrhizal fungi and phosphorus on drought-induced oxidative stress and 14-3-3 proteins gene expression of Populus cathayana - Han, Yanyan; Zhang, Wenrui; Xu, Tingying; Tang, Ming (Frontiers in Microbiology, 2022)
The application of arbuscular mycorrhizal fungi (AM fungi) and phosphorus (P) can improve plant growth under drought stress by upregulating the antioxidant system and osmotic accumulation. 14-3-3 protein can respond to different abiotic stresses such as low P and drought. The purpose of this experiment was to study the effects of AM fungi (Rhizophagus intraradices) inoculation on reactive oxygen species (ROS) homeostasis, P metabolism, and 14-3-3 gene expression of Populus cathayana at different P levels and drought stress (WW: well-watered, WD: water deficit). Under WD conditions, AM fungi inoculation significantly increased the P content in leaves and roots, but the benefit in roots is limited by the level of P addition, and the roots may have more alkaline phosphatase and phytase under P stress, and these activities in the rhizosphere soil inoculated with AM fungi were stronger. Under WD conditions, the activities of catalase (leaf and root) and peroxidase (root) inoculated with AM fungi were significantly higher than those without inoculation and decreased with P addition. 14-3-3 genes PcGRF10 and PcGRF11 have a positive correlation with the antioxidant system, osmotic regulation, and P metabolism, which may be more significant after inoculation with AM fungi. Our results provide new insights into the mechanism of ROS homeostasis and P metabolism in mycorrhizal plants under drought stress.